V 240 EL: improved Costeño corn for green corn cob production - Trujillo-Campos, Alberto; Gómez-Montiel, Noel Orlando; Cantú Almaguer, Miguel Angel; Hernández-Galeno, César del Ángel; Vázquez-Carrillo, María Gricelda (Revista Mexicana de Ciencias Agrícolas, 2022)
The state of Morelos ranks second in area sown (9 687 ha) with corn for green corn cob nationwide. Costeño corn is used in the state for the production of green corn cob, this corn is an interracial complex of the Tabloncillo, Vandeño, Tuxpeño and Tepecintle races, and still has some negative characteristics in the phenotype of the plant. Faced with this situation, the objective of subjecting Costeño corn to genetic improvement was set to reduce undesirable aspects in the phenotype of the plant. From 2004, a cycle of mass selection and four cycles of recurrent selection of families of maternal half-siblings were carried out; subsequently, five cycles of individual selection, it was possible to reduce the intrinsic agronomic problems of Costeño corn, this allowed making its varietal description in the years from 2013 to 2015 and obtaining, in 2019, the registration number 3876-MAZ-2081-130319/C and the denomination V 240 EL in the National Catalogue of Plant Varieties, likewise, the breeder’s title number 2314. V 240 EL has intermediate-tall size (251-300 cm), early-intermediate biological cycle (120 days), male flowering of 56-60 days and the female flowering two days later, white grain with toothed texture, yields of green corn cob and grain of 15.1 and 6 t ha-1, respectively. The V 240 EL variety adapts to the environmental conditions of the low (dry tropics) and intermediate (subhumid subtropics) zones of the state of Morelos and similar regions of the neighboring states of Guerrero, Puebla and State of Mexico.